The effects of board and ownership structure on corporate R & D strategy : a Malaysian-based evidence / Roslida Ramlee - Ramlee, Roslida (2001)
This study is adapted from a study conducted by Baysinger et.al.(1991) on selected American companies. The purpose of this study is to analyze the relationship and examine the factors that are expected to influence a firms' corporate R & D strategy, namely board composition and firm's ownership structure. For board composition, this study is find out whether inside or outside directors influence the R & D spending. Firm ownership structure is also examined to see whether all substantial shareholders, individual shareholders or institutional shareholders influence the R & D spending. A sample of 40 companies of various industries, listed on the Kuala Lumpur Stock Exchange (KLSE) Main Board and Second Board were investigated. The Pearson Product Moment Correlation and Multiple Linear Regression analysis are used to analyze the data obtained from the annual reports of the respective companies and KLSE Handbook for the years 1990-1999. The overall result of this study indicates that there is no significant relationship that exists between the board composition and firm's ownership structure on corporate R & D spending of a company. The overall implication of the result indicates that more than 90% of corporate R & D decisions are influenced by other factors unexplained in this study. The findings at 95% confidence level indicated that all null hypotheses cannot be accepted. Regardless of other insignificant results obtained, it is hoped that this study will be a Malaysian-based evidence to support the study on the relationship between board composition and ownership structure on corporate R & D spending.